Aryl hydrocarbon receptor-deficient mice are protected from high fat diet-induced changes in metabolic rhythms. (16th March 2017) - Jaeger, Cassie; Xu, Canxin; Sun, Mingwei; Krager, Stacey; Tischkau, Shelley A.
ABSTRACT: High fat diet (HFD) consumption alters the synchronized circadian timing system resulting in harmful loss, gain or shift of transcriptional oscillations. The aryl hydrocarbon receptor (AhR) shares structural homology to clock genes, containing both PAS domains and basic helix-loop helix structural motifs, allowing for interaction with components of the primary circadian feedback loop. Activation of AhR alters circadian rhythmicity, primarily through inhibition of Clock/Bmal1-mediated regulation of Per1. AhR-deficient mice are protected from diet-induced metabolic dysfunction, exhibiting enhanced insulin sensitivity and glucose tolerance. This study examined whether AhR haploinsufficiency can also protect against diet-induced alterations in rhythm. After feeding AhR+/+ and AhR+/− mice an HFD (60% fat) for 15 weeks, samples were collected every 4 hours over a 24-hour period. HFD altered the rhythm of serum glucose and the metabolic transcriptome, including hepatic nuclear receptors Rev-erbα and PPARγ in wild-type c57bl6/j mice. AhR reduction provided protection against diet-induced transcriptional oscillation changes; serum glucose and metabolic gene rhythms were protected from the disruption caused by HFD feeding. These data highlight the critical role of AhR signaling in the regulation of metabolism and provide a potential therapeutic target for diseases characterized by rhythmic desynchrony.